2005
DOI: 10.1142/s0129054105003133
|View full text |Cite
|
Sign up to set email alerts
|

State Complexity of Concatenation and Complementation

Abstract: We investigate the state complexity of concatenation and the nondeterministic state complexity of complementation of regular languages. We show that the upper bounds on the state complexity of concatenation are also tight in the case that the first automaton has more than one accepting state. In the case of nondeterministic state complexity of complementation, we show that the entire range of complexities, up to the known upper bound can be produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…In [15] it has been shown that all values from log n to 2 n can be reached, however, appropriate automata have been defined over a growing alphabet of size 2 n+1 . In this section, we prove that this result still holds for a fixed five-letter alphabet.…”
Section: Complementmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15] it has been shown that all values from log n to 2 n can be reached, however, appropriate automata have been defined over a growing alphabet of size 2 n+1 . In this section, we prove that this result still holds for a fixed five-letter alphabet.…”
Section: Complementmentioning
confidence: 99%
“…Motivated by the magic number problem for nfa-to-dfa construction, we examined a similar question for complements of regular languages in [15]. Using a growing alphabet of size 2 n+1 we proved that all values in the range from log n to 2 n can be obtained as the nondeterministic state complexity of the complement of an n-state nfa language.…”
Section: Introductionmentioning
confidence: 99%
“…Many results related to the state complexity of various operations on formal languages have been examined. We note in particular that the state complexity of concatenation was obtained by Maslov [10] and further studied by Yu et al [16] and Jirásek et al [7], who determined the effect of the number of final states on the state complexity. The state complexity of concatenation over a unary alphabet was considered by Yu et al [16] and subsequently by Pighizzini and Shallit [11], while Holzer and Kutrib [6] have studied the state complexity of concatenation with respect to nondeterministic finite automata (NFA).…”
Section: Introductionmentioning
confidence: 83%
“…The precise worst case state complexity of many basic language operations has been established; see e.g. [2,5,8,14,17,23,25,27,31,33,37]. Also there has been much work on the state complexity of combinations of basic language operations [3,7,9,10,18,32].…”
Section: Introductionmentioning
confidence: 99%